Rare case of type I hypersensitivity reaction to sodium hypochlorite solution in a healthcare setting. (21st October 2016) - Chia Shi Zhe, Gabriel; Green, Andrew; Fong, Yuke Tien; Lee, Haur Yueh; Ho, Sweet Far
Abstract : Sodium hypochlorite is a clear yellowish solution with a characteristic odour of chlorine and is commonly used as a disinfectant and a bleaching agent. It is used in various healthcare settings for its fast-acting and broad-spectrum antimicrobial activity. It is a known irritant and there are some reports that it can also cause allergic contact dermatitis of type IV hypersensitivity. We report a case of work-related type I hypersensitivity to sodium hypochlorite, presenting with recurrent urticarial rash and a positive prick test reaction to this chemical. He was subsequently excused from further exposure with no further recurrences of the urticarial rash. To the best of our knowledge, this is the first such reported case due to work in the healthcare setting.